A hora dos intelectuais : literatura, política e engajamento no Brasil (1964-1967) - Czajka, Rodrigo [UNESP] (My University, 2013)
The resistance to the military dictatorship in Brazil (1964-1985) had many faces, especially among intellectuals. This article will discuss the activity of some writers and journalists in the process of articulation as leftist intellectuals in opposition to the military regime, as "cultural resistance" in various forms assumed in the context of politicization of culture and cultural goods market in the mid 1960´s.

A resistência à ditadura militar no Brasil (1964-1985) teve inúmeras faces, sobretudo, nos meios intelectualizados. Neste artigo será debatida a atividade de alguns escritores e jornalistas no processo de articulação como intelectuais de esquerda na oposição ao regime militar, como “resistência cultural” assumida em variadas formas no contexto de politização da cultura e do mercado de bens culturais em meados da década de 1960.
The time of the intellectuals literature, press and engagement in Brazil (1964-1967)